STUDY OF THE OPERATING TIME OF THE PROTECTIVE COATING OF SURFACES OF ASSEMBLY AND WELDING EQUIPMENT - Vjacheslav Romenskiy; Viktoriia Nevliudova; Elena Persiyanova (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The subject of the study is the issues related to determining the service life of protective coatings protecting the surfaces of assembly and welding fixtures from the effects of welding spatter and mechanical wear when performing certain assembly and welding operations of welded metal structures. The development in Ukraine of various industries, especially the precision engineering industry (instrument making), is characterized by a transition to market management methods, increasing demand for competitive and liquid products. This can be achieved by the systematic and rapid introduction of technically new products, improving their quality, increasing labor productivity, and automating production. Welded metal structures are widely used in the designs of modernized and new types of products, the high-quality production of which is impossible without the use of assembly and welding equipment.  The reliability and durability of these devices depends on the protection of their surfaces to the effects of welding spatter and scoring during assembly and welding operations. Analytical and experimental studies of the resistance of protective coatings to an experimental welding drop of metal showed that of the most tested coatings, the most durable is the developed protective coating containing a mixture of molybdenum disulfide powder, graphite powder, epoxy varnish and certain solvents. Purpose: determination of the service life of the developed protective coating when exposed to a number of significant factors, including the effects of real welding spatter. Tasks: to identify the main - significant technological factors affecting the service life of the protective coating;  develop a planning matrix based on a full factorial experiment;  to conduct experimental studies of the resistance of the coating to the effect of an experimental metal drop under the influence of significant technological factors, to obtain the equations of regression of resistance;  conduct analytical and experimental studies to determine the temperature of the experimental drop of molten metal;  conduct analytical studies of the temperature of a real welding spray;  conduct a study of the resistance to friction;  conduct analytical studies to determine the quantitative characteristics of the reliability and durability of the proposed coating composition. Results: the article presents the research data by the authors of the service life of the proposed protective coating that protects the surfaces of assembly and welding fixtures when exposed to welding spatter and coating wear when moving metal structures in the fixture.  The quantitative characteristics of the reliability and durability of the coating are obtained. Conclusions: A methodology has been developed for determining the service life of protective coatings protecting the surfaces of assembly and welding fixtures from the effects of welding spatter during welding operations and coating wear when moving elements of the welding structure in the fixture during assembly.